Histone Deacetylase Inhibitors Stimulate Dedifferentiation of Human Breast Cancer Cells Through WNT/β‐Catenin Signaling123. (22nd October 2012) - Debeb, Bisrat G.; Lacerda, Lara; Xu, Wei; Larson, Richard; Solley, Travis; Atkinson, Rachel; Sulman, Erik P.; Ueno, Naoto T.; Krishnamurthy, Savitri; Reuben, James M.; Buchholz, Thomas A.; Woodward, Wendy A.
Abstract: Recent studies have shown that differentiated cancer cells can dedifferentiate into cancer stem cells (CSCs) although to date no studies have reported whether this transition is influenced by systemic anti‐cancer agents. Valproic acid (VA) is a histone deacetylase (HDAC) inhibitor that promotes self‐renewal and expansion of hematopoietic stem cells and facilitates the generation of induced pluripotent stem cells from somatic cells and is currently being investigated in breast cancer clinical trials. We hypothesized that HDAC inhibitors reprogram differentiated cancer cells toward the more resistant stem cell‐like state. Two highly aggressive breast cancer cell lines, SUM159 and MDA‐231, were sorted based on aldehyde dehydrogenase (ALDH) activity and subsequently ALDH‐negative and ALDH‐positive cells were treated with one of two known HDAC inhibitors, VA or suberoylanilide hydroxamic acid. In addition, primary tumor cells from patients with metastatic breast cancer were evaluated for ALDH activity following treatment with HDAC inhibitors. We demonstrate that single‐cell‐sorted ALDH‐negative cells spontaneously generated ALDH‐positive cells in vitro. Treatment of ALDH‐negative cells with HDAC inhibitors promoted the expansion of ALDH‐positive cells and increased mammosphere‐forming efficiency. Most importantly, it significantly increased the tumor‐initiating capacity of ALDH‐negative cells in limiting dilution outgrowth assays. Moreover, while HDAC inhibitors upregulated β‐catenin expression and significantly increased WNT reporter activity, a TCF4 dominant negative construct abolished HDAC‐inhibitor‐induced expansion of CSCs. These results demonstrate that HDAC inhibitors promote the expansion of breast CSCs through dedifferentiation and have important clinical implications for the use of HDAC inhibitors in the treatment of cancer. STEM CELLS 2012;30:2366–2377